2010
DOI: 10.1684/abc.2010.0430
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A, -B, -DRB1 alleles and haplotypes frequencies in Moroccan patients with leukemia

Abstract: Previous studies have demonstrated some significant differences in HLA allele frequencies in leukemic patients and normal subjects. In Moroccan leukemic patients, the frequency of HLA alleles has not already been determined. We have analyzed HLA class I and class II alleles and haplotypes in 62 Moroccan leukemic patients and 98 unrelated normal subjects using PCR-SSO method. Significant positive association with the disease, in patients compared to controls, was found for three alleles: HLA-B*44 (12.7% vs 6.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Therefore, they considered this allele as it may be protective against leukemia, whereas DRB1*03, DRB1*04, DRB1*13 has been moderately increased in patients. It therefore might be regarded as susceptible alleles in leukemia disease 26 .This research results was contradictory to another study which find that in CML patients, the haplotype HLA-DRB1 * 0101/DQA1 * 0104/DQB1 * 05011 were significantly more common than controls 14 .…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, they considered this allele as it may be protective against leukemia, whereas DRB1*03, DRB1*04, DRB1*13 has been moderately increased in patients. It therefore might be regarded as susceptible alleles in leukemia disease 26 .This research results was contradictory to another study which find that in CML patients, the haplotype HLA-DRB1 * 0101/DQA1 * 0104/DQB1 * 05011 were significantly more common than controls 14 .…”
Section: Discussioncontrasting
confidence: 68%
“…The function of these classes is activate the immune response by encoding membrane glycoproteins that act as mediators in the presentation of antigenic peptides to lymphocytes T CD8+ and T CD4+ respectively [ 12 ]. Thanks to multiple studies on the subject, we know that the HLA complex plays a role in AL pathogenesis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HLA alleles could be important genetic risk factors for AML and ALL patients. A study of a Moroccan population found that HLA-B*44 may be a presumptive predisposing factor in the development of leukemia [ 13 ]. By contrast, a Turkish study found that HLA-B*13 and HLA-B* 40 alleles were negatively associated with AML [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial dataset on HLA-related leukemias is available. Studies have demonstrated links between HLA-DPB1*02:01 (8), DRB1*04 (9-13), DQB1*04 (14), B44 (15), DRB1*13 (15), and predisposition to acute leukemia development. Nevertheless, currently, no HLA allele or haplotype has found clinical application as a diagnostic or prognostic factor in leukemia.…”
Section: Introductionmentioning
confidence: 99%